2022
DOI: 10.1083/jcb.202203139
|View full text |Cite
|
Sign up to set email alerts
|

Plant autophagosomes mature into amphisomes prior to their delivery to the central vacuole

Abstract: Autophagosomes are double-membraned vesicles that traffic harmful or unwanted cellular macromolecules to the vacuole for recycling. Although autophagosome biogenesis has been extensively studied, autophagosome maturation, i.e., delivery and fusion with the vacuole, remains largely unknown in plants. Here, we have identified an autophagy adaptor, CFS1, that directly interacts with the autophagosome marker ATG8 and localizes on both membranes of the autophagosome. Autophagosomes form normally in Arabidopsis thal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…The phenotypic consequence of fyve3 mutation is not evident unless it is combined with fyve2 mutation, which prevented us and others from identifying its involvement in autophagy ( Kim et al., 2022 ; Zhao et al., 2022 ). In our previous work ( Kim et al., 2022 ), we employed 48-h nitrogen starvation for autophagic flux assay, whereas 24-h starvation was used for the assay in this study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The phenotypic consequence of fyve3 mutation is not evident unless it is combined with fyve2 mutation, which prevented us and others from identifying its involvement in autophagy ( Kim et al., 2022 ; Zhao et al., 2022 ). In our previous work ( Kim et al., 2022 ), we employed 48-h nitrogen starvation for autophagic flux assay, whereas 24-h starvation was used for the assay in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, we observed a similar suppression in the autophagic flux analysis in which 21-d-old leaves of fyve2 fyve3 mutants were used ( Kim et al., 2022 ). Zhao et al. (2022) reported that the steady-state level of the autophagic cargo receptor NBR1 was comparable between fyve2 and fyve2 fyve3 , but did not directly assess the autophagic flux of fyve2 fyve3 (i.e., cfs1 cfs2 ) double mutants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations